Evacuation of victims in mass events and disasters - Witold Pawłowski; Krzysztof Goniewicz; Mariusz Goniewicz; Robert Czerski; Dorota Lasota (Kazimierz Wielki University, 2018)
The tasks of health in mass events, disasters and emergency Situations ensue from the specific nature of each event, which determines the scale of the needs and difficulties needed to refrain. Emergency medical procedures at the mass event and disasters called the doctrine of conduct mass loss, requires a complete change in thinking and withdrawal from the Generally Accepted Principles of treatment From the efficient organization of the rescue operation depends on the success of the entire treatment process. The aid time and providing the victims of the accident to the hospital usually we decides about the fate of the victim. The article presents the medical rescue activities used during mass accidents and disasters and discusses the Principles of evacuation.